Improved virtual flux direct power control of three phase PWM rectifier using SOGI-FLL estimator under disturbed voltage conditions - A Rahab; H Benalla; F Senani (Institute of Advanced Engineering and Science, 2019)
In this paper, improved sonsorless direct power control (DPC) of three-phase rectifiers is presented. The new system are based on virtual flux (VF) and notch filter using Second Order Generalized Integrator frequency located loop SOGI-FLL estimator. In order to improve the VF-DPC performance of PWM rectifier, an improved observation method of virtual flux-linkage is proposed. To avoid the relevant problems of pure integrator, and to achieve the accurate observation of the grid voltage’s phase, (SOGI-FLL) are used to displace the pure integrator. Theoretical principles of this method are presented and discussed. These strategies are also investigated under disturbed grid voltage. A theoretical analysis of active and reactive power under a non-ideal source is clearly demonstrated. In order to calculate the compensated powers, the extraction of positive, negative, and harmonic sequences of voltage and current is needed and a multiple dual SOGI-FLL method is used for rapid and accurate extraction. It is shown that the VFDPC with integrating notch filter exhibits several advantages, particularly providing small ripple of DC-link voltage and sinusoidal line current when the supply voltage is not ideal.